Uniqueness and stability of harmonic maps and their Jacobi fields - Jäger, Willi; Kaul, Helmut (Manuscripta mathematica, 1979)
Let M, N be Riemannian manifolds and let f1, f2: M→N be harmonic maps. Using a maximum principle, an estimate of the distances of these maps by the distances of their boundary values will be proved. Corresponding estimates will be stated for the norm of Jacobi fields along harmonic maps, and for the distances of solutions of the heat equation.